Model Pembelajaran Klasikal Baca-Simak Di TPQ Fauzul Qur’an Nogosari Pandaan - Nikita Silvi Yohana Putri; Achmad Yusuf (Impressive: Journal of Education, 2024)
Education is a shared responsibility between families and the surrounding community. In the learning process there must be sources and guidelines, namely the Qur'an and as-Sunnah. Learning the Qur'an must be instilled in children as early as possible, because the Qur'an is one of the holy books revealed by Allah SWT. This study aims to 1) Knowing the process of learning classical reading and listening at TPQ Fauzul Qur'an, 2) Knowing supporting activities in TPQ Fauzul Qur'an, 3) Knowing the advantages and disadvantages of the classical learning model of reading read. This study uses qualitative-descriptive research with a case study approach because the researcher immediately went to TPQ Fauzul Qur'an to get the data. The data collected in the form of 1) Observation, 2) Interview, 3) Documentation. The results obtained include: 1) The process of applying the classical learning model to read read at TPQ Fauzul Qur'an, this process focuses more on the teacher, 2) Supporting activities at TPQ Fauzul Qur'an, while the activities include: (a) Reading Asmaul Husna pronunciation together, (b) muroja'ah short letters and selected verses, (c) darling or traveling tadarus, 3) The advantages and disadvantages of the classical learning model are taken from two points of view, namely the teacher and students.